Morphometric Analysis of Corpus Callosum with Magnetic Resonance Imaging in Children; Correlation with Age and Gender - Hatice Arıöz Habibi; Ozan Berk Gül; Emine Calışkan; Mehmet Öztürk (Galenos Publishing House, 2021)
Objective: Corpus Callosum (CC) is a dynamic organ that undergoes morphological modifications throughout life which must be taken into account for appropriate evaluation of CC. The objectives of this study were to provide normative data about the morphological modifications in CC during childhood and to evaluate possible differences related to age and sex. Methods: In this retrospective study, cranial MRI studies of 320 children (160 boys, and 160 girls) between 2 to 17 years old with normal neurologic examination findings were reviewed. We divided the age groups as increments of 1 year, and included 10 girls and 10 boys, in each age group. The following parameters were measured on midsagittal T1-weighted images: area of CC (CCA), supracallosal area (SCA), length of CC (LCC), genu thickness (GT), body thickness (BT), splenium thickness (ST), ratio of genu thickness to splenium thickness (GT/ST) and a novel parameter termed callosal index (CCA/SCA). These parameters were correlated with age and sex. Results: All parameter values increased with age. After age 10, there was no evident age or gender-related changes between groups, except for the 15-year-old group. When we appraised all age groups, we determined that CCA and SCA were larger in boys but the callosal index did not differ between genders. Conclusion: This is the first study which used the modified callosal index in the pediatric age group. Callosal index gives the opportunity to make brain size corrections according to the individual and allows a more accurate and personal measurement in the follow-up of the same individual. This study offers an objective assessment measure.